Increasing Peak Flow of Snyder Synthetic Hydrograph Units in the Serenan Sub-Watershed of Bengawan Solo Watershed - Barid, Burhan; Okta Afanda, Brillyana (Universitas Ibn Khaldun Bogor, 2022)
Changes in land use are closely related to the increasing number of people who are increasing from time to time. This land use change has an impact on increasing the runoff coefficient because the rain that falls will not be retained or seep and flows directly into the river. This is what causes an increase in peak discharge in a watershed. The purpose of this study was to determine the magnitude of changes in peak discharge that occurred in the Serenan watershed in 2015 and 2021 due to changes in land use. The method used in analyzing the peak discharge is the Snyder unit hydrograph, the results of this method will be compared with the measured unit hydrograph to determine the correlation between the two. To make a synthetic unit hydrograph, non-physical parameters are needed in the form of Ct and Cp values. The Ct value used in 2015 was 2.30 and in 2021 it was 2.00 while the Cp value in 2015 was 0.90 and in 2021 it was 1.10. The results of the analysis using the Snyder method showed that the peak discharge was 139.61 m3/s in 2015 and 194.56 m3/s in 2021. The analysis shows that the peak discharge increased by 54.95 m3/s and has a very strong correlation with the hydrograph of the measured unit.